2021
DOI: 10.3390/biom11010080
|View full text |Cite
|
Sign up to set email alerts
|

Role of Retinoic Acid Signaling, FGF Signaling and Meis Genes in Control of Limb Development

Abstract: The function of retinoic acid (RA) during limb development is still debated, as loss and gain of function studies led to opposite conclusions. With regard to limb initiation, genetic studies demonstrated that activation of FGF10 signaling is required for the emergence of limb buds from the trunk, with Tbx5 and RA signaling acting upstream in the forelimb field, whereas Tbx4 and Pitx1 act upstream in the hindlimb field. Early studies in chick embryos suggested that RA as well as Meis1 and Meis2 (Meis1/2) are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Meis2 regulates genes involved in retinoic acid production in the LGE SVZ Retinoic acid (RA), a small molecule derived from vitamin A, is a ligand for nuclear RA receptors, and has been proposed to play important roles in striatal neurogenesis (Berenguer and Duester, 2021;Chatzi et al, 2011;Liao et al, 2008;Oulad-Abdelghani et al, 1997;Toresson et al, 1999;Urban et al, 2010;Waclaw et al, 2004). RA is synthesized by Raldh3 (Aldh1a3) in LGE progenitors at E12.5 (Molotkova et al, 2007;Toresson et al, 1999), and the Gsx2 TF is required for Aldh1a3 expression (Waclaw et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Meis2 regulates genes involved in retinoic acid production in the LGE SVZ Retinoic acid (RA), a small molecule derived from vitamin A, is a ligand for nuclear RA receptors, and has been proposed to play important roles in striatal neurogenesis (Berenguer and Duester, 2021;Chatzi et al, 2011;Liao et al, 2008;Oulad-Abdelghani et al, 1997;Toresson et al, 1999;Urban et al, 2010;Waclaw et al, 2004). RA is synthesized by Raldh3 (Aldh1a3) in LGE progenitors at E12.5 (Molotkova et al, 2007;Toresson et al, 1999), and the Gsx2 TF is required for Aldh1a3 expression (Waclaw et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was previously found that artificially increased expression of Hnf4a is able to reverse hepatic liver failure in rats, while also restoring expression of a highly interconnected TF network including Hnf1a and Cebpa which supports the identified interactions [ 65 , 66 ]. Two of the yet unknown TFs in DILI are Meis Homeobox 1 (Meis1) and Meis Homeobox 2 (Meis2) which are generally known in a developmental context [ 67 , 68 ]. However, their down-regulation in early pathogenesis is supported by enriched TF activity, differential expression before adverse histopathology as well as upstream regulators which are also enriched before adverse histopathology.…”
Section: Resultsmentioning
confidence: 99%
“…FGF‐8 is involved in the process of cartilage generation, which is mediated by the interaction between FGF‐8 and FGFR, especially FGFR1 and FGFR3. The effect is determined to the difference in signalling pathway strength; FGFR1 mainly regulates catabolism, while FGFR3 mainly regulates anabolism 5,8,49–51 . FGFR3 is expressed in proliferating chondrocytes.…”
Section: Overview Of Fgf‐8 In Normal Cartilagementioning
confidence: 99%
“…These results suggest that the classical Wnt signalling pathway exerts a negative feedback effect on regulating the proliferation and differentiation of FGF‐8‐stimulated chondrocytes. Wnt‐mTOR and NF‐κβ also produce acid‐sensing ion channels 1A (ASIC1A) under acidic conditions to promote the apoptosis of chondrocytes 49,50,83,84 …”
Section: Overview Of Fgf‐8 In Normal Cartilagementioning
confidence: 99%